Epistemic stance markers in corporate social responsibility reports: a discourse analysis of energy sector communications - Liu, Shuai (Frontiers in Communication, 2026)
This study examines epistemic stance markers (ESM) in Corporate Social Responsibility (CSR) reports, focusing on how energy companies manage uncertainty and establish credibility in sustainability communications. Using Marín-Arrese’s classification framework, I analyzed 10 CSR reports (152,084 words) from Fortune 500 energy companies (2014–2018) through directed content analysis, identifying four categories of epistemic stance markers. The analysis revealed 357 epistemic stance markers: modal expression markers (58.8%), external source markers (20.2%), mental state verbs (19.6%), and inferential markers (1.4%). This distribution reflects strategic patterns prioritizing uncertainty management and external validation for reputation management. Epistemic stance markers function as sophisticated reputation management tools in high-scrutiny industries, enabling companies to balance stakeholder accountability with operational flexibility. This research provides the first systematic examination of epistemic stance markers in CSR reports, addressing a significant gap in business discourse analysis and contributing to corporate communication theory.